Identification of ankyrin-transmembrane-type subfamily genes in Triticeae species reveals TaANKTM2A-5 regulates powdery mildew resistance in wheat - Hu, Ping; Ren, Yueming; Xu, Jun; Wei, Qichao; Song, Puwen; Guan, Yuanyuan; Gao, Huanting; Zhang, Yang; Hu, Haiyan; Li, Chengwei (Frontiers in Plant Science, 2022)
The ankyrin-transmembrane (ANKTM) subfamily is the most abundant subgroup of the ANK superfamily, with critical roles in pathogen defense. However, the function of ANKTM proteins in wheat immunity remains largely unexplored. Here, a total of 381 ANKTMs were identified from five Triticeae species and Arabidopsis, constituting five classes. Among them, class a only contains proteins from Triticeae species and the number of ANKTM in class a of wheat is significantly larger than expected, even after consideration of the ploidy level. Tandem duplication analysis of ANKTM indicates that Triticum urartu, Triticum dicoccoides and wheat all had experienced tandem duplication events which in wheat-produced ANKTM genes all clustered in class a. The above suggests that not only did the genome polyploidization result in the increase of ANKTM gene number, but that tandem duplication is also a mechanism for the expansion of this subfamily. Micro-collinearity analysis of Triticeae ANKTMs indicates that some ANKTM type genes evolved into other types of ANKs in the evolution process. Public RNA-seq data showed that most of the genes in class d and class e are expressed, and some of them show differential responses to biotic stresses. Furthermore, qRT-PCR results showed that some ANKTMs in class d and class e responded to powdery mildew. Silencing of TaANKTM2A-5 by barley stripe mosaic virus-induced gene silencing compromised powdery mildew resistance in common wheat Bainongaikang58. Findings in this study not only help to understand the evolutionary process of ANKTM genes, but also form the basis for exploring disease resistance genes in the ANKTM gene family.